IN SEARCH OF THE LOST COUNTRY. SOME REMARKS ON THE NOVEL DER TURM (THE TOWER) BY UWE TELLKAMP - Kałążny, Jerzy (Porównania, 2014)
The article presents the German literary reactions to the German unification in 1990 and dissolution of the East German state. It is focused on the novel Der Turm. Geschichte aus einem versunkenen Land (2008) by Uwe Tellkamp, his dealing with literary traditions (among others with utopia) and with narrative patterns.